(untitled) (EAAE Joint Publishings, 2026)
n response to the escalating energy costs associated with air conditioning, architects and researchers increasingly turn to passive cooling strategies, emphasizing effective heat reduction, shading, and natural ventilation. One possibility is to introduce elements from vernacular architecture around the world into different climates. This study is aiming to evaluate the performance of a traditional element from hot arid climates to hot- humid climates. The traditional Mashrabiya screens from the Arabic architecture used to mitigate high indoor temperatures while regulating sunlight and preventing glare. Four screens were prototyped with controlled perforation parameters, utilizing Rhinoceros 3D and Computer Numerical Control (CNC) technology. The screens were produced with varying perforation percentages and thicknesses. A testbed reflecting common U.S. construction techniques was constructed for assessment, incorporating indoor and outdoor sensors measuring temperature, air velocity, humidity, and light intensity. The methodology included controlled airflow laboratory testing and outdoor testing that lasted a minimum of 48 hours for each screen, alongside a control scenario without any screen. Air movement was generated for laboratory testing using Surfer software for multiple scenarios to understand the effect on the indoor air speed when using the different screens. The collected data revealed diverse performances among the screens. The screen with 30% perforation and a 10 cm thickness demonstrated the best performance, effectively moderating indoor temperature and distributing light. Screens with the very high perforation percentages allowed for elevated air temperatures, while those with minimal perforation did not generate sufficient airflow. However, the screens struggled to maintain comfortable indoor humidity levels during high humid outdoor conditions, prompting further investigation into enhancing performance in high humidity. The study establishes a basis for further research on developing screens that can help mitigate hot and humid climates to create comfortable indoor environments.